PENGARUH INFORMATION QUALITY, APPS AESTHETICS, ISLAMIC PHYSICAL ATTRIBUTES TERHADAP DIGITAL OPENING ACCOUNT BANK SYARIAH DI INDONESIA YANG DIMEDIASI OLEH TRUST OF CONSUMER - Royyanto, Afif; Kornitasari, Yenny (Islamic Economics and finance in Focus, 2023)
This study investigates the effects of information quality, app aesthetics, and Islamic physical attributes on consumer trust in digital opening account services offered by Sharia banks in Indonesia. The results suggest that only two factors play a significant role in shaping consumer trust and that trust acts as a mediator in the relationship between these factors and consumer adoption of digital banking services in the Sharia banking sector in Indonesia. This research used single equation model and partial least square on statistics for processing the data and analysis. The findings have implications for both practitioners and researchers, highlighting the importance of information quality , app aesthetics, and Islamic physical attributes in building consumer trust in digital banking services in the Islamic banking finance industry.